Application of New Techniques for Fracture-Vug Effictiveness Analysis Based on Micro Resistivity Imaging Logging in the Dengying Formation - MO Jing; XIE Bing; LAI Qiang; WANG Dali; WANG Yue (Cejing jishu)
The secondary pores occurred in post-sediment deposition are very heterogeneous in the Sinian Dengying carbonate formation of Gaoshiti-Moxi area in Sichuan basin, which has caused significant test production differences. Conventional logging and seismic data have lots of limitation in Dengying carbonate reservoir effectiveness analysis, but the advanced technology about secondary pore-fracture effectivity analysis can solve this problem. Surface porosity, size and connectedness parameter curves of effective pore-fracture can be calculated through the advanced technology. The key point of this advanced technology is that fake information like muddy, pyrite, induced fracture and breakout can be distinguished and removed, and only remains unfilled effective pores by selecting an appropriate threshold value based on core calibration. The result shows the new technology for analyzing the effectiveness of fractures and vugs can accurately evaluate the effectiveness of fractures and vugs near the wellbore, and the effectiveness analysis results of fractures and vugs are highly consistent with the core in Gaoshiti-Moxi area. In addition, an attempt is made to use the effectiveness parameters and open flow rate as inputs, and IPSOM is used to explore and analyze the relationship between open flow rate level, reservoir effective parameters, and reservoir thickness, forming a preliminary method for predicting open flow rate levels.